Considering climate-driven weather implications on lobster harvesting effort in Nova Scotia - Gregor Reid; Mark Flaherty; Leah Lewis-McCrea; Therese Wilson; Debora Lucatelli; James Cunningham (Marine Policy, 2026)

A decade of continuous Rockall Trough transport observations using moorings and gliders - Kristin Burmeister; Sam C. Jones; Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham; Lewis A. Drysdale; Mark E. Inall; Tiago S. Dotto; N. Penny Holliday (Ocean Science, 2026)
The Rockall Trough, northwest of Scotland and Ireland, is a key conduit for the North Atlantic Current (NAC) and European Slope Current (ESC) transporting heat and salt toward the Nordic Seas and Arctic Ocean while mediating exchanges between the open ocean and the European shelf. We present a decade-long record of Rockall Trough circulation from the Ellett Array providing the first continuous estimates of heat and freshwater transport between 2014 and 2024. We develop a methodology that combines the high spatial resolution of gliders with the high temporal resolution of moorings and ocean reanalysis output producing continuous eastern boundary velocity fields of the ESC for integration into the full Rockall Trough transport product. This approach improves the mean structure of the ESC, capturing the southward undercurrent previously unresolved and enhancing the ability to reproduce extreme, likely mesoscale, transport events. The Rockall Trough transport is dominated by the NAC flowing through the mid basin, exhibiting multi-year variability consistent with changes in the subpolar gyre and the mid-2010s cold freshwater anomaly. The ESC acts as a secondary driver, is not correlated with the NAC and is influenced by along-slope wind stress. Since 2022, warmer and saltier conditions, amplified by the 2023 extreme North Atlantic marine heatwave, have strengthened northward volume, heat, and salt transport through the Ellett Array. Our results highlight the value of sustained glider-based boundary current observations for Atlantic climate monitoring and demonstrate that the combined mooring–glider framework provides a robust and transferable approach for long-term ocean transport monitoring.

Assessment of the anticonvulsant activity of Myrica gale L., a traditional Irish plant in ethnoveterinary medicine, using a 4-AP induced seizure, electrophysiological model, in vitro - Sophie Whyms; Gaia Scalabrino; Kate Connor; Shipra Nagar; Maria Pigott; Helen Sheridan; Mark Cunningham (Phytochemistry Letters, 2025)

Accumulation of benzotriazole UV-stabilizers in relation to ingested plastics and associated health metrics in Larus gulls feeding at a landfill in Atlantic Canada - Kerry Schutten; André Morrill; Zhe Lu; Akshaya Chandrashekar; Joshua T. Cunningham; Gregory J. Robertson; Mark L. Mallory; Claire M. Jardine; Jennifer F. Provencher (Journal of Hazardous Materials, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Microbial fuel cells to monitor natural attenuation around groundwater plumes - Panagiotis Kirmizakis; Mark Cunningham; Deepak Kumaresan; Rory Doherty (Environmental Science and Pollution Research, 2025)
This research presents a straightforward and economically efficient design for a microbial fuel cell (MFC) that can be conveniently integrated into a borehole to monitor natural attenuation in groundwater. The design employs conventional, transparent, and reusable PVC bailers with graphite tape and granular activated carbon to create high surface area electrodes. These electrodes are connected across redox environments in nested boreholes through a wire and variable resistor setup. The amended electrodes were installed in pre-existing boreholes surrounding a groundwater plume near a former gasworks facility. Among all the MFC locations tested, the MFC at the plume fringe exhibited the highest electrical response and displayed significant variations in the differential abundance of key bacterial and archaeal taxa between the anode and cathode electrodes. The other MFC configurations in the plume center and uncontaminated groundwater showed little to no electrical response, suggesting minimal microbial activity. This straightforward approach enables informed decision-making regarding effectively monitoring, enhancing, or designing degradation strategies for groundwater plumes. It offers a valuable tool for understanding and managing contaminant degradation in such environments.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Community-level responses and environmental fate of metformin in freshwater mesocosms - Nicholas C. Blandford; Vince Palace; José Luis Rodríguez-Gil; Lauren Timlick; Madeline Stanley; Richard A. Frank; Sheena Campbell; Martina Rudy; Stephanie Marshall; Abby Wynia; Thomas Clark; Jessie Cunningham; et al. (Science of The Total Environment, 2024)

The BirdLife Seabird Tracking Database: 20 years of collaboration for marine conservation - Ana P.B. Carneiro; Maria P. Dias; Bethany L. Clark; Elizabeth J. Pearmain; Jonathan Handley; Amy R. Hodgson; John P. Croxall; Richard A. Phillips; Steffen Oppel; Joanne M. Morten; Ben Lascelles; Cleo Cunningham; et al. (Biological Conservation, 2024)

Plastic ingestion, accumulated heavy metals, and health metrics of four Larus gull species feeding at a coastal landfill in eastern Canada - Kerry Schutten; André Morrill; Akshaya Chandrashekar; Brian Stevens; E. Jane Parmley; Joshua T. Cunningham; Gregory J. Robertson; Mark L. Mallory; Claire Jardine; Jennifer F. Provencher (Journal of Hazardous Materials, 2024)

Effects of metformin on wild fathead minnows (Pimephales promelas) using in-lake mesocosms in a boreal lake ecosystem - Erin Ussery; Mark McMaster; Vince Palace; Joanne Parrott; Nicholas C. Blandford; Richard Frank; Karen Kidd; Oana Birceanu; Joanna Wilson; Mehran Alaee; Jessie Cunningham; Abby Wynia; et al. (Science of The Total Environment, 2024)

Reasons for meal termination, eating frequency, and typical meal context differ between persons with and without a spinal cord injury - Gary J. Farkas; Paige M. Cunningham; Alicia M. Sneij; John E. Hayes; Mark S. Nash; Arthur S. Berg; David R. Gater; Barbara J. Rolls (Appetite, 2024)

Intersex manifestation in the rainbow darter (Etheostoma caeruleum): Are adult male fish susceptible to developing and recovering from intersex after exposure to endocrine active compounds? - Keegan A. Hicks; Meghan L.M. Fuzzen; Hadi A. Dhiyebi; Leslie M. Bragg; Patricija Marjan; Jessie Cunningham; Mark E. McMaster; Nivetha Srikanthan; Kirsten E. Nikel; Maricor J. Arlos; Mark R. Servos (Aquatic Toxicology, 2023)

Observation-based estimates of volume, heat, and freshwater exchanges between the subpolar North Atlantic interior, its boundary currents, and the atmosphere - Sam C. Jones; Neil J. Fraser; Stuart A. Cunningham; Alan D. Fox; Mark E. Inall (Ocean Science, 2023)
The Atlantic Meridional Overturning Circulation (AMOC) transports heat and salt between the tropical Atlantic and Arctic oceans. The interior of the North Atlantic subpolar gyre (SPG) is responsible for the much of the water mass transformation in the AMOC, and the export of this water to intensified boundary currents is crucial for projecting air–sea interaction onto the strength of the AMOC. However, the magnitude and location of exchange between the SPG and the boundary remains unclear. We present a novel climatology of the SPG boundary using quality-controlled CTD (conductivity–temperature–depth) and Argo hydrography, defining the SPG interior as the oceanic region bounded by 47∘ N and the 1000 m isobath. From this hydrography we find geostrophic flow out of the SPG around much of the boundary with minimal seasonality. The horizontal density gradient is reversed around western Greenland, where the geostrophic flow is into the SPG. Surface Ekman forcing drives net flow out of the SPG in all seasons with pronounced seasonality, varying between 2.45 ± 0.73 Sv in the summer and 7.70 ± 2.90 Sv in the winter. We estimate heat advected into the SPG to be between 0.14 ± 0.05 PW in the winter and 0.23 ± 0.05 PW in the spring, and freshwater advected out of the SPG to be between 0.07 ± 0.02 Sv in the summer and 0.15 ± 0.02 Sv in the autumn. These estimates approximately balance the surface heat and freshwater fluxes over the SPG domain. Overturning in the SPG varies seasonally, with a minimum of 6.20 ± 1.40 Sv in the autumn and a maximum of 10.17 ± 1.91 Sv in the spring, with surface Ekman the most likely mediator of this variability. The density of maximum overturning is at 27.30 kg m−3, with a second, smaller maximum at 27.54 kg m−3. Upper waters (σ0 27.54 kg m−3) exiting to the south. Our results support the present consensus that the formation and pre-conditioning of Subpolar Mode Water in the north-eastern Atlantic is a key determinant of AMOC strength.

Wild fish responses to wastewater treatment plant upgrades in the Grand River, Ontario - Kirsten E. Nikel; Gerald R. Tetreault; Patricija Marjan; Keegan A. Hicks; Meghan L.M. Fuzzen; Nivetha Srikanthan; Emily K. McCann; Hadi Dhiyebi; Leslie M. Bragg; Pam Law; Dominika Celmer-Repin; Sonya Kleywegt; et al. (Aquatic Toxicology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Comparison Between Ground, Helicopter, and Unmanned Aircraft System Magnetic Datasets: A Case Study from the Abitibi Greenstone Belt, Canada - Michael Cunningham; Claire Samson; Jeremy Laliberté; Mark Goldie; Alan Wood; David Birkett (Pure and Applied Geophysics, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Why disease ecology needs life‐history theory: a host perspective - Andrés Valenzuela‐Sánchez; Mark Q. Wilber; Stefano Canessa; Leonardo D. Bacigalupe; Erin Muths; Benedikt R. Schmidt; Andrew A. Cunningham; Arpat Ozgul; Pieter T.J. Johnson; Hugo Cayuela (Ecology Letters, 2021)
When facing an emerging infectious disease of conservation concern, we often have little information on the nature of the host‐parasite interaction to inform management decisions. However, it is becoming increasingly clear that the life‐history strategies of host species can be predictive of individual‐ and population‐level responses to infectious disease, even without detailed knowledge on the specifics of the host‐parasite interaction. Here, we argue that a deeper integration of life‐history theory into disease ecology is timely and necessary to improve our capacity to understand, predict and mitigate the impact of endemic and emerging infectious diseases in wild populations. Using wild vertebrates as an example, we show that host life‐history characteristics influence host responses to parasitism at different levels of organisation, from individuals to communities. We also highlight knowledge gaps and future directions for the study of life‐history and host responses to parasitism. We conclude by illustrating how this theoretical insight can inform the monitoring and control of infectious diseases in wildlife.

Inversion of Magnetic Data Acquired with a Rotary-Wing Unmanned Aircraft System for Gold Exploration - Michael Cunningham; Claire Samson; Jeremy Laliberté; Mark Goldie; Alan Wood; David Birkett (Pure and Applied Geophysics, 2021)

Significance of Climate Indices to Benthic Conditions Across the Northern North Atlantic and Adjacent Shelf Seas - Clare Johnson; Mark Inall; Stefan Gary; Stuart Cunningham (Frontiers in Marine Science, 2020)

Inferring seasonal infection risk at population and regional scales from serology samples - Mark Q. Wilber; Colleen T. Webb; Fred L. Cunningham; Kerri Pedersen; Xiu‐Feng Wan; Kim M. Pepin (Ecology, 2020)
Accurate estimates of seasonal infection risk can be used by animal health officials to predict future disease risk and improve understanding of the mechanisms driving disease dynamics. It can be difficult to estimate seasonal infection risk in wildlife disease systems because surveillance assays typically target antibodies (serosurveillance), which are not necessarily indicative of current infection, and serosurveillance sampling is often opportunistic. Recently developed methods estimate past time of infection from serosurveillance data using quantitative serological assays that indicate the amount of antibodies in a serology sample. However, current methods do not account for common opportunistic and uneven sampling associated with serosurveillance data. We extended the framework of survival analysis to improve estimates of seasonal infection risk from serosurveillance data across population and regional scales. We found that accounting for the right‐censored nature of quantitative serology samples greatly improved estimates of seasonal infection risk, even when sampling was uneven in time. Survival analysis can also be used to account for common challenges when estimating infection risk from serology data, such as biases induced by host demography and continually elevated antibodies following infection. The framework developed herein is widely applicable for estimating seasonal infection risk from serosurveillance data in humans, wildlife, and livestock.

Sublethal effects of natural parasitism act through maternal, but not paternal, reproductive success in a wild population - Olivia Hicks; Jonathan A. Green; Francis Daunt; Emma J. A. Cunningham; Mark Newell; Adam Butler; Sarah J. Burthe (Ecology, 2019)
Parasites are a major component of all animal populations. Males and females often differ in their levels of parasite prevalence, potentially leading to sex differences in the impact of parasitism on fitness, with important implications for the evolution of parasite and host traits including resistance, tolerance, and virulence. However, quantitative measures of the impact of parasitism under free‐living conditions are extremely rare, as they require detailed host demographic data with measures of parasite burden over time. Here, we use endoscopy for direct quantification of natural‐parasite burdens and relate these to reproductive success over 7 yr in a wild population of seabirds. Contrary to predictions, only female burdens were associated with negative impacts of parasitism on breeding success, despite males having significantly higher burdens. Female reproductive success declined by 30% across the range of natural parasite burdens. These effects persisted when accounting for interannual population differences in breeding success. Our results provide quantitative estimates of profound sub‐lethal effects of parasitism on the population. Importantly, they highlight how parasites act unpredictably to shape ecological and evolutionary processes in different components of the same population, with implications for demography and selection on host and parasite traits.

Large-scale forcing of the European Slope Current and associated inflows to the North Sea - Robert Marsh; Ivan D. Haigh; Stuart A. Cunningham; Mark E. Inall; Marie Porter; Ben I. Moat (Ocean Science, 2017)
The European Slope Current provides a shelf-edge conduit for Atlantic Water, a substantial fraction of which is destined for the northern North Sea, with implications for regional hydrography and ecosystems. Drifters drogued at 50 m in the European Slope Current at the Hebridean shelf break follow a wide range of pathways, indicating highly variable Atlantic inflow to the North Sea. Slope Current pathways, timescales and transports over 1988–2007 are further quantified in an eddy-resolving ocean model hindcast. Particle trajectories calculated with model currents indicate that Slope Current water is largely recruited from the eastern subpolar North Atlantic. Observations of absolute dynamic topography and climatological density support theoretical expectations that Slope Current transport is to first order associated with meridional density gradients in the eastern subpolar gyre, which support a geostrophic inflow towards the slope. In the model hindcast, Slope Current transport variability is dominated by abrupt 25–50 % reductions of these density gradients over 1996–1998. Concurrent changes in wind forcing, expressed in terms of density gradients, act in the same sense to reduce Slope Current transport. This indicates that coordinated regional changes of buoyancy and wind forcing acted together to reduce Slope Current transport during the 1990s. Particle trajectories further show that 10–40 % of Slope Current water is destined for the northern North Sea within 6 months of passing to the west of Scotland, with a general decline in this percentage over 1988–2007. Salinities in the Slope Current correspondingly decreased, evidenced in ocean analysis data. Further to the north, in the Atlantic Water conveyed by the Slope Current through the Faroe–Shetland Channel (FSC), salinity is observed to increase over this period while declining in the hindcast. The observed trend may have broadly compensated for a decline in the Atlantic inflow, limiting salinity changes in the northern North Sea during this period. Proxies for both Slope Current transport and Atlantic inflow to the North Sea are sought in sea level height differences across the FSC and between Shetland and the Scottish mainland (Wick). Variability of Slope Current transport on a wide range of timescales, from seasonal to multi-decadal, is implicit in sea level differences between Lerwick (Shetland) and Tórshavn (Faroes), in both tide gauge records from 1957 and a longer model hindcast spanning 1958–2012. Wick–Lerwick sea level differences in tide gauge records from 1965 indicate considerable decadal variability in the Fair Isle Current transport that dominates Atlantic inflow to the northwest North Sea, while sea level differences in the hindcast are dominated by strong seasonal variability. Uncertainties in the Wick tide gauge record limit confidence in this proxy.

Virtual Electrode Recording Tool for EXtracellular potentials (VERTEX): comparing multi-electrode recordings from simulated and biological mammalian cortical tissue - Richard J. Tomsett; Matt Ainsworth; Alexander Thiele; Mehdi Sanayei; Xing Chen; Marc A. Gieselmann; Miles A. Whittington; Mark O. Cunningham; Marcus Kaiser (Brain Structure and Function, 2015)

Psittacine beak and feather disease in a free-living ring-necked parakeet (Psittacula krameri) in Great Britain - Ricardo C. C. Sa; Andrew A. Cunningham; Mark P. Dagleish; Nick Wheelhouse; Ann Pocknell; Nicole Borel; Hannah L. Peck; Becki Lawson (European Journal of Wildlife Research, 2014)

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Reduction of metastasis using a non-volatile buffer - Arig Ibrahim Hashim; Heather H. Cornnell; Maria de Lourdes Coelho Ribeiro; Dominique Abrahams; Jessica Cunningham; Mark Lloyd; Gary V. Martinez; Robert A. Gatenby; Robert J. Gillies (Clinical & Experimental Metastasis, 2011)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Effect of Well Orientation (Vertical vs. Horizontal) and Well Length on the Injection of CO2 in Deep Saline Aquifers - Roland Okwen; Mark Stewart; Jeffrey Cunningham (Transport in Porous Media, 2011)

Analytical model for screening potential CO2 repositories - Roland T. Okwen; Mark T. Stewart; Jeffrey A. Cunningham (Computational Geosciences, 2011)

Transcriptome Profiling of Selectively Bred Pacific Oyster Crassostrea gigas Families that Differ in Tolerance of Heat Shock - R. Paul Lang; Christopher J. Bayne; Mark D. Camara; Charles Cunningham; Matthew J. Jenny; Christopher J. Langdon (Marine Biotechnology, 2009)

Effect of soil biota on growth and allocation by Eucalyptus microcarpa - Mark Bourne; Adrienne B. Nicotra; Matthew J. Colloff; Saul A. Cunningham (Plant and Soil, 2008)

Genetic consequences of habitat fragmentation and loss: the case of the Florida black bear (Ursus americanus floridanus) - Jeremy D. Dixon; Madan K. Oli; Michael C. Wooten; Thomas H. Eason; J. Walter McCown; Mark W. Cunningham (Conservation Genetics, 2007)

Anatomical evidence for androdioecy in the clam shrimp Eulimnadia texana - Naida Zucker; Mark Cunningham; Henry P. Adams (Hydrobiologia, 1997)